Laro Ng Lahi Through the Lens of Junior High School Students: A Phenomenological Inquiry - Myra F. Ruin; Victoria E. Tamban; Marcial M. Bandoy (Research Synergy Foundation Press, 2024)
Junior high school students’ knowledge, attitudes, and perceptions of traditional games are crucial to explore, and their integration into curriculum programs can optimize learning and developmental outcomes. This study aimed to understand and explore the lived experiences of junior high school students regarding their attitude and engagement toward Laro ng Lahi and its cultural significance. Laro ng Lahi has become unfamiliar or is no longer recognized by today’s generation. The researcher aimed to emphasize the love for traditional games. Traditional games, such as Luksong baka, jump over the person (baka) or